Prediction of Pressure-Viscosity Coefficient of Mixtures - Shinichiro Hayashi; Kazuo Masuhara; Sobahan Mia; Shigeki Morita; Nobuyoshi Ohno (Tribology Online, 2008)
The pressure-viscosity coefficient α is one of the most important property for EHL condition, however its measurement has difficulty. Therefore authors attempt to predict α for blend oils by using the relationship between pressure-viscosity coefficient and logarithm of kinematic viscosity at atmospheric pressure, which is used for single oil as ever. The pressure-viscosity coefficient of mixtures enables to predict with base oils properties and viscosity of mixture at atmospheric pressure. Test fluids are SN-HV, PBSN, DOS, BBPH and mixtures of these oils. High-pressure viscosity measurement was done at pressure up to 0.4 GPa and temperature range at 20°C to 100°C. The authors proposed the prediction method of α for mixtures.